The book review of A whole New light by Sandra brown - Nurendra, Demashetareza (LANTERN (Journal on English Language, Culture and Literature), 2016)
This book review has been created to find the strength and the weakness in A Whole New Life written by Sandra Brown.. The strengths are located on the theme and the main characters, named Cyn and Worth The weakness appears from the epilog. The theme is found through the dialogues delivered by Worth and Cyn.. The main characters have function to be the object where the problem lies in.